Bacteremia with an Unusual Pathogen: Mycobacterium neoaurum - Hesham Awadh; Munthir Mansour; Mahmoud Shorman (Case Reports in Infectious Diseases, 2016)
Mycobacterium neoaurum (M. neoaurum) is an infrequently encountered cause of infection in humans. It is a member of the rapidly growing mycobacteria family. It predominately afflicts those with a compromised immune status and a chronically indwelling vascular access. Isolation of this organism is challenging yet the advent of 16s ribosomal sequencing paved the way for more sensitive detection. No treatment guidelines are available and treatment largely depends on the experience of the treating physician and nature of the isolate. We report a case of M. neoaurum bacteremia in an immune competent host, with a chronically placed peripherally inserted central catheter (PICC line).